Triptorelin in the Relief of Lower Urinary Tract Symptoms in Advanced Prostate Cancer Patients: The RESULT Study - Alexandre Peltier; Fouad Aoun; Vincent De Ruyter; Patrick Cabri; Roland Van Velthoven (Prostate Cancer)
This prospective, noninterventional, open-label, multicentre, Belgian study assessed the prevalence of moderate to severe lower urinary tract symptoms (LUTS) in patients with locally advanced or metastatic prostate cancer scheduled to receive triptorelin therapy and its effects on LUTS were evaluated focusing on symptom relief and changes in quality of life (QOL) related to urinary symptoms (November 2006 to May 2010). Inclusion criteria were age >18 years, histologically confirmed advanced or metastatic prostate cancer, and life expectancy ≥12 months. Exclusion criteria were treatment with any LHRH analogue within the last 6 months or any other investigational agent within the last 3 months before study entry. Patients who received one or more triptorelin doses and had one or more efficacy assessments were evaluated. In total, 325 patients were included with a median age of 74 years (50 to 95 years). Mean age at first diagnosis was 73±8 years. Moderate (IPSS 8–19) to severe (IPSS ≥ 20) LUTS were observed in 62% of patients. Triptorelin reduced LUTS severity. This improvement was perceived within the first 24 weeks of treatment and was maintained after 48 weeks. A decrease in PSA level was also observed.